Management of labor and delivery - Macones, George A. (Chichester, West Sussex ; Hoboken, NJ : Wiley Blackwell, 2016)
The process of labor and delivery has been one of the most perilous activities in human life. The awkward evolutionary compromises giving rise to humans makes birthing potentially life threatening for both mother and child. Despite the development of modern care, labor and delivery continues to be a dangerous process even though the levels of fatality have decreased over the past several decades. This clinically focused guide to modern labor and delivery care covers low and high-risk situations, the approach of the team in achieving a successful outcome and what to consider when quick decisions have to be made. Aimed at both trainee and practicing obstetrician-gynecologists, this new edition includes practical guidance such as algorithms, protocols, and quick-reference summaries. It is squarely focused on the process of birth and concentrates on modern clinical concerns, blending science with clinical applications.
Antenatal preparation for labor / Molly Stout, Jessica C. Garrett, and David M. Stamilio -- Normal labor and delivery / Shu Qin Wei, Jun Zhang, Romy-Leigh McMaster, and William D. Fraser -- Management of labor and delivery in low risk subjects / Anthony Shanks and Alison Cahill -- Induction and augmentation of labor / Karin A. Fox, Mildred M. Ramirez, and Susan M. Ramin -- Fetal monitoring and assessment / Alison Cahill -- Operative vaginal delivery / Katherine R. Goetzinger, and George A. Macones -- Cesarean delivery / Methodius G. Tuuli and Molly J. Stout -- Trial of labor after cesarean / William Grobman and Emily Miller -- Malpresentation and malposition / Yvonne W. Cheng and Aaron B. Caughey -- Multiple gestations / Laura Houston and Roger Newman -- Obstetrical emergencies / Christina S. Han and Christian M. Pettker -- Surgical management of obstetrical emergencies / Laurie S. Swaim and Gary A. Dildy, III -- Maternal disorders affecting labor and delivery / Audrey Merriam and Anthony Sciscione -- Fetal disorders affecting labor and delivery / Audrey Merriam and Anthony Sciscione -- Labor and delivery management of the obese gravida / Jordan H. Perlow, Megan Jones, and John Ozimek -- Intrapartum and post-partum infections / Scott A. Sullivan and Christopher Goodier -- Obstetric anesthesia / Emily J. Baird, Richard C. Month, and Valerie A. Arkoosh -- Postpartum care / Audrey Lyndon, Kirsten Wisner, and Kristina J. Hung -- Development of an obstetrical patient safety program / Christian M. Pettker and Edmund F. Funai.
Preceeded by Management of labor and delivery / [edited by] Robert K. Creasy, c1997.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher, and Wiley Online Library edition.
Keywords: Labor, Obstetric; Delivery, Obstetric; Labor (Obstetrics); Delivery (Obstetrics); Childbirth; Childbirth; Delivery (Obstetrics); Labor (Obstetrics); MEDICAL / Gynecology & Obstetrics; Medical; Electronic books